Schottariella Mirifica P.C. Boyce & S. Y. Wong: A New Name for Schottarum Sarikeense (Araceae: Schismatoglottideae) - Peter C., Boyce; Sin Yeng, Wong (SpringerOpen Journal, 2009)
The recent publication of the new genus Schottarum (Araceae) from Sarawak, Malaysian Borneo (Boyce and Wong 2008), contains a serious typification error by which Schottarum is a taxonomic synonym of Schismatoglottis and a new generic name is required for the taxon we described as Schottarum. The names Schottariella and Schottariella mirifica are here published.